Planning for Construction Logistics An evaluation and development of a construction logistics plan at Serneke - ANDERSSON, OSKAR; Nilsson, Andreas (My University, 2018)
The construction industry in Sweden has a turnover of 639 billion SEK, which corresponds to an increase of 71 % over the last decade. Moreover, Sweden is the fastest urbanising country in all of Europe. Increasing construction within dense cities results in complex processes. Congestion at sites, delayed deliveries and coordination of the supply chain are stated to be some of the main logistics issues in the industry, which suffers from low productivity and efficiency. Therefore, this thesis aims to identify logistical challenges in urban city construction projects for the construction company Serneke and how their logistical processes could be developed to cope with these challenges. Further, the study contributes to the understanding of construction logistics and its importance for Serneke to achieve a successful project outcome. In order to reach results that align with the aim of the thesis, an abductive research method was chosen, comprising a literature review followed by site observations at four of Serneke’s projects and interviews with employees at Serneke in different positions. In total, 11 interviews were performed in the study. The findings from the study show that the processes differ between the projects and the organisation, and the projects have implemented dedicated logistical solutions to a varying extent. Furthermore, the project based nature of the industry seems to lack standardised processes for construction logistics where the logistical responsibility seldom is connected to one person at the site, resulting in un-announced deliveries and a planning that does not correspond with the reality. In order to increase the productivity and efficiency of construction logistics, the contractor has the responsibility of coordinating the activities throughout the project process. A construction logistics plan, is one solution to ensure an efficient logistics process. The plan is a tool for coordinating logistics to overcome the obstacles of congestion on construction sites by addressing how to use e.g. Just in Time, construction consolidation centres, and dedicated planning systems. In addition, standardising a planning and execution process simplifies the transition between projects and the processes it entails. There is still much to improve within construction logistics. Therefore, one suggestion is to investigate key ratios regarding logistics and what economical figures logistics tools could contribute with.
Keywords: Samhällsbyggnadsteknik; Civil Engineering